IMPLEMENTASI GOOD HOUSEKEEPING (GHK) UNTUK PENGEMBANGAN POTENSI DESA WISATA MELALUI PAKET WISATA DAN EDUKASI BATIK DI DESA KALIPUCANG KABUPATEN BATANG - Mutadin Mutadin; Maghfiroh Maghfiroh; Sri Puji Astuti (LPPM Universitas Pekalongan, 2020)
Tourism and the existence of an area are two interrelated components. Tourism sites build the image of an area and influence the socio-economic community and the area. Kalipucang is a village that is famous as a center for batik production in Kabupaten Batang. This village has the potential to become an education tourism village. The development of educational-based tourism is in accordance with one of the 9 superior work programs of Bupati Kabupaten Batang in 2017 - 2022, namely the revitalization of tourism objects and building new educational destinations that are educational, based on community empowerment. Many concepts of science in Batik there are owned by the Kalipucang, need to be balanced with the existence of a good concept of batik production management. One of them is Good Housekeeping (GHK) which deals with several practical steps to improve operational performance, improve organizational learning procedures and improve occupational safety and health. This concept management can reflect the identity of tourism and education packages in Kalipucang. The purpose of this study is to identify the socio-economic conditions and the availability of facilities and infrastructure that support the implementation of GHK in Kalipucang, Kabupaten Batang, find out the results of the SWOT analysis in Kalipucang, implementing the GHK concept as the development of educational tourism potential in the of Kalipucang village. The results in of this study are recommendations: the GHK concept in Kalipucang in the form of an eco-map of the batik industry. From the data analysis, the GHK concept application was carried out at one location used for batik learning media for visitors coming to the Kalipucang. Then, a replication of the development plans of other villages has the potential for educational tourism in the field of batik in Kabupaten Batang Regency.